An unexpected role of IL10 in mesoderm induction and differentiation from pluripotent stem cells: Implications in zebrafish angiogenic sprouting, vascular organoid development, and therapeutic angiogenesis - Kaiyuan Niu; Chengxin Zhang; Chenxin Liu; Wei Wu; Yi Yan; Ancheng Zheng; Silin Liu; Zhenning Shi; Mei Yang; Wen Wang; Qingzhong Xiao (European Journal of Cell Biology)
Mesoderm induction is a crucial step for vascular cell specification, vascular development and vasculogenesis. However, the cellular and molecular mechanisms underlying mesoderm induction remain elusive. In the present study, a chemically-defined differentiation protocol was used to induce mesoderm formation and generate functional vascular cells including smooth muscle cells (SMCs) and endothelial cells (ECs) from human induced pluripotent stem cells (hiPSCs). Zebrafish larvae were used to detect an in vivo function of interleukin 10 (IL10) in mesoderm formation and vascular development. A three dimensional approach was used to create hiPSC-derived blood vessel organoid (BVO) and explore a potential impact of IL10 on BVO formation. A murine model hind limb ischemia was applied to investigate a therapeutic potential of hiPSC-derived cells treated with or without IL10 during differentiation. We found that IL10 was significantly and specifically up-regulated during mesoderm stage of vascular differentiation. IL10 addition in mesoderm induction media dramatically increased mesoderm induction and vascular cell generation from hiPSCs, whereas an opposite effect was observed with IL10 inhibition. Mechanistic studies revealed that IL10 promotes mesoderm formation and vascular cell differentiation by activating signal transducer and activator of transcription 3 signal pathway. Functional studies with an in vivo model system confirmed that knockdown of IL10 using morpholino antisense oligonucleotides in zebrafish larvae caused defective mesoderm formation, angiogenic sprouting and vascular development. Additionally, our data also show IL10 promotes blood vessel organoid development and enhances vasculogenesis and angiogenesis. Importantly, we demonstrate that IL10 treatment during mesoderm induction stage enhances blood flow perfusion recovery and increases vasculogenesis and therapeutic angiogenesis after hind limb ischemia. Our data, therefore, demonstrate a regulatory role for IL10 in mesoderm formation from hiPSCs and during zebrafish vascular development, providing novel insights into mesoderm induction and vascular cell specifications.